The cases of non-equivalence between English and Lithuanian: a corpus based solution - Cvilikaitė, Jurgita (Kalbotyra, 2007)
Machine translation systems, machine-readable dictionaries or other computer-oriented electronic lexical resources present a challenging task in the case of the Lithuanian language. Many of them are related to the problem of non-equivalence resulting from cultural and systemic differences and thus existing on various levels of a language – lexical, morphological and syntactic. This paper focuses on instances of non-equivalence between Lithuanian and English on the morphological level. More specifically, the resolution of non-equivalence problems caused by morphological gaps between English and Lithuanian is investigated. Morphological gaps represent a type of lexical gaps, which are understood as lack of direct lexicalisation for a certain concept.The paper is written with two goals in mind. First, I would like to present the phenomenon of lexical gaps and its subtype, morphological gaps, its relation to translation. Second, I wish to compare how these cases are rendered in bilingual dictionaries and in texts, i.e. in the parallel English-Lithuanian corpus. The comparison leads to certain recommendations for translators, lexicographers and other researchers working on human language technologies.This contrastive study is corpus based. Corpus linguistics is one of the most popular methods in modern linguistics. Pragmatically it is beneficial to a researcher – in a corpus (monolingual or multilingual) it is possible instantaneously to see numerous examples of a word in use. Quantitative and qualitative analysis of such data allows one to judge the collocational and colligational patterns a word forms, as well as its semantic and prosodic preference (for more about the theoretic postulates of corpus linguistics, see Sinclair 1996, Stubbs 2001). A multilingual corpus (comparative or parallel) provides a linguist with invaluable information about two (or more) languages – interesting similarities and, most importantly, contrasts significant for further language description.